(untitled) (Research, Society and Development, 2026)
The Internal Affairs Division is responsible for planning, coordinating, supervising, and carrying out activities related to the investigation of disciplinary transgressions and military criminal offenses, preserving ethics, legality, and discipline within the Military Police. In this context, the internship functions as a pedagogical tool that links theory and practice, allowing cadets to experience real situations and develop technical and professional skills. This study aimed to investigate the feasibility and benefits of implementing an internal affairs internship in the PMAL Officer Training Course curriculum, focusing on the development of competencies related to investigative processes and procedures within the corporation. The methodology included bibliographic and documentary research, collection of statistical data from the PMAL General Internal Affairs Division, and structured questionnaires applied to 54 cadets. The results showed limited contact with internal affairs content, predominantly insufficient knowledge of administrative and disciplinary procedures, and a low perception of preparedness to work in such investigations. Most participants stated that they fully believed (55.6%) or believed (40.7%) that practical experience in internal affairs would contribute to their professional training. In addition, institutional data revealed recurring returns of case files for supplementary measures. It is concluded that implementing an internal affairs internship in the PMAL Officer Training Course is a strategic measure to strengthen the integration between theory and practice, improve professional training, and reinforce a culture of legality, ethics, and institutional efficiency.